Foot health: new approaches to prevention in young athletes - Lutkov V.F. ,; Smirnov G.I. ,; Shadrin D.I. ,; Miller L.L. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to creation of a multifaceted approach to prevent and treat foot arch problems in young athletes engaged in team sports. Methods and structure of the study. Plantography methods, Romberg test, and mathematical statistics method (Microsoft Office Excel and Stats Graphics) were used. The objects of the study were young football players aged 9-10 years old from the Junior football school and volleyball players aged 12-13 years from the Ekran school and Nevskie Zvezda school. There are 36 young athletes in total. Results and conclusions. It has been confirmed that to effectively prevent and treat foot problems in young athletes engaged in sports, it is crucial to identify potential risk factors. The primary risk factor for foot arch disorders is the impact forces experienced when the foot contacts the ground during running and jumping, which exceed the adaptive capacity of the foot's connective tissues, muscles, and bones. Muscle weakness and compromised ligament and tendon elasticity can result in flat feet, leading to various types of lower limb overuse injuries in young athletes. To prevent the development of foot arch pathology, a comprehensive exercise program has been developed, which includes: 1) exercises without weight-bearing on the feet; 2) exercises with weight-bearing on the feet; 3) exercises for the feet using objects.. Through a comparative examination of the evolution of the degree of foot arch impairment following the implementation of the devised exercise regimen, it was determined that there was a positive trend: a reduction in the severity of flat feet was observed in 54.7% of football players and 97.5% of volleyball players.